New Records of the Hotson's Jerboa Allactaga hotsoni, Thomas, 1920 (Rodentia: Dipodidae) from Khorasan and Yazd Provinces, Iran (Journal of Sciences, Islamic Republic of Iran)
A total of five specimens of Allactaga hotsoni were captured in Khorasan and Yazd provinces, Iran, in summer 2004 and 2005. The specimens are similar to those described previously from Baluchistan of Iran and Afghanistan. For the first time a karyological study was carried out to make a comparison with the other species. On the basis of karyological study there is not any significant difference in chromosome number from other species of Allactaga (2n=48, NFa=92). Previously this species was reported from Baluchistan and National Kavir Park near Siah-Kuhe. In this study A. hotsoni is reported for the first time from the study areas.